FLORISTIC AND FUNCTIONAL-REPRODUCTIVE DIVERSITY OF ARBOREAL AND SHRUB SPECIES USED IN THE ORNAMENTATION OF SQUARES OF THE SÃO RAIMUNDO NONATO CITY, PIAUÍ, BRAZIL. (Terr@ Plural, 2021)
We evaluated the urban green area of the São Raimundo Nonato city, Piauí, regarding the floristic composition and the pollination service, comparing it with the natural ecosystem (Caatinga), through indices of functional diversity of the reproductive traits. For that, the usual procedures of collect and identification of species, classification (the origin, floral attributes, and pollination syndromes), followed by data analysis. The results show that the urban area presents a greater functional diversity because of the richness of exotic species, but with specialized pollination systems and resources inaccessible to native pollinators. By removing them, the rates are higher in the Caatinga, revealing the need for planning in afforestation with native species suggested.
Keywords: urban areas; pollination; functional diversity